Minutes of Advisory Workshop on E-Commerce - Smith, Nadine Eriksson (AHRC Research Centre for Studies in Intellectual Property and Technology Law, 2003)
Minutes of the Advisory Workshop on E-Commerce, chaired by Edwards, held in Edinburgh in 2003.
Keywords: Minutes; E-Commerce